La desproporcionalidad de las sanciones previstas en el Código Orgánico Integral Penal contra el delito de cohecho entre el oferente y retribuyente incide en el cometimiento del delito contra la eficiencia de la administración pública. - Ortega, Stalin J. (2022)
This scientific article seeks to identify the causes for committing the crime of bribery, a criminal type regulated in the Organic Comprehensive Criminal Code. It is necessary to understand the nature of the exceptions that exist in the prosecution of the crime of bribery. These exceptions are the imprescriptibility of the action and the sentence, and the power to continue a process in the absence of the defendant; regulations that exist even when their application is in direct conflict with basic rights; such as the right to defense and due process. The main problem that has been addressed is the analysis of the crime of bribery in order to determine if this criminal provision has had an effective result in the fight against corruption and unethical activities of authorities, public servants and the payer, and if the sanctions imposed are proportional to both the offeror and the payer; considering that it seemed to be the objective of the legislator for its creation, so if this objective has not been achieved, it may be time to analyze whether this regulation is effective and necessary. That is to say, in our reality it is notorious that when the corrupt initiate criminal proceedings, they obtain privileged information and flee from justice. It is intended to demonstrate how the sanction established in Art. 280 of the Organic Comprehensive Criminal Code is not proportional between the offeror and the payer, sanctioning the public servant, leaving the businessman who offered the bribe in impunity, persisting the social and economic damage that affects to the protected legal interest.